Actor network theory, construction of meanings and some aspects of non-ordered space: exploring the boundaries of responsive built environment (2015)
This article examines the processes of transformation of the architecture and spatial character of a Nigerian city, in the planning and delivery of a sustainable built environment. It examines the inter-dependency or relationship between the traditional market space and the city which is constantly being challenged, adapted and simultaneously undermined by the city’s rapid growth and modernisation. The process of change towards modernisation led to the demolition of existing traditional market structures.to give way to ‘modern’ ones without any reference to the ritualistic or cultural significance of these markets or the interests of market users. Using methodological tools provided by combination of Actor Network theory (ANT) and interpretive anthropology in gaining insight into how various actants in the built marketplace, live and interact together to shape the city. This article traces historical changes in the surrounding urbanscape of the market, in particular the location of developments, many originating from the colonial period, of adjacent or nearby civic/commercial buildings and educational institutions and their impact on the life of the city and market over time. Findings suggest that the meanings attached to the market and its built environment has not only changed on several levels from the symbolic, sacred, religious use to commercial and mundane one, but also has taken on new sp'atial forms due to the activities of the various actors which is predicated on their worldview. The article conpludes that theoretical and cultural interpretation impacts the physical marketplace, its form, character and spatiality; this must itself be understood as an agent or actant in the struggle, in as much as it both enables and constrains human activities.